Cross-cultural application of a practice-oriented acquiescence measure - Krautz, Carolin; Hoffmann, Stefan (International marketing review, 2019)
Purpose Extant research shows that acquiescence response style (ARS) is culture-bound and may bias the results of comparative cross-cultural studies. Conventional measures of ARS are difficult to apply in practice. To overcome this limitation, the purpose of this paper is to propose an alternative, practice-oriented measure, namely, pARS. The authors apply Hofstede’s cultural dimensions (Hofstede et al., 2010) to test whether pARS is culture-bound. The cross-cultural study provides a high level of cross-cultural generalisability due to the extensive number of surveyed countries (n=30) and subjects (n=236.089). The authors run multi-level analysis to identify within- and between-country-level predictors. Design/methodology/approach On the individual level, the authors use data of a large-scale cross-cultural study, including 236.089 consumers from 30 countries worldwide. The authors apply several methods to test for the culture-boundness of pARS. First, they apply correlation analysis to replicate existing cross-cultural results and to ensure nomological validity. Second, applying ordinary least square regression, the authors simultaneously test the six Hofstede cultural dimensions (Hofstede et al., 2010) and investigate interactions between the dimensions. Finally, they use multi-level analysis to confirm the stability of culture-bound results, controlling for individual- and country-level variability. Findings The paper introduces an alternative measure for acquiescence (pARS), which is particularly suitable for shorter questionnaires. A large-scale consumer study with 236.089 respondents in 30 countries supports the culture-bound validity of pARS. The authors confirm construct validity and the nomological network of pARS. Contrasting existing studies, multi-level analysis demonstrates that a high level of power distance majorly leads to ARS. Therefore, cross-cultural researchers need to control for ARS in countries high in power distance, especially when paired with high uncertainty avoidance. Originality/value A large-scale consumer study with 236.089 respondents from 30 countries shows that respondents from various countries differ significantly in their level of acquiescence. The study confirms that power distance is the most relevant cultural dimension to explain these differences. Although ARS may bias the results of comparative cross-cultural studies, it is rarely controlled by market research studies outside the academic realm. The present work proposes and establishes the validity of a practice-oriented measure of acquiescence, namely, pARS. pARS is particularly suitable for shorter questionnaires. In contrast to prior approaches, applying pARS does not require adding non-substantive items to the questionnaire.